O ônus da prova na ação civil pública: hipóteses de flexibilização - Souza, Landolfo Andrade de (2013)
There is no doubt that the modern civil procedure must be updated to cope with the substantive law needs and the new contemporary society dynamics. Likewise, such changes dispense legislative modifications, which often take a long time to be made. Thus, it s necessary to pursue the procedure s improvement by a more appropriate managing of the procedural techniques available for the judge, in the light of the constitutional guarantees. The rule for the burden of proof is within this perspective: it s one of the matters to which the doctrine devotes its attention in order to make the indispensable transformations in the procedural system to bring it closer to substantive law s reality. To this end, this work searched to examine how the burden of proof operates in the class actions, studying the reasons that authorize its change, since such possibility beyond the realm of consumer law - may correspond to a significant condition of effective protection of collective interests. For that purpose, one has used law doctrine, case law and deductive, inductive and analogical methods. The Federal Constitution and federal rules related to the burden of proof dogma and the collective interests protection have also been examined. The research has been split in for main parts. Firstly, some relevant aspects of the collective procedure have been studied. Then, the structural elements of the burden of proof have been analysed. The third part was dedicated to the conceptual elements, as well as the fundaments of applicability, including de lege lata, of the dynamic burden of proof theory in Brazilian law were outlined. In the fourth part, it has been demonstrated that the hipotheses that allow the flexibility of the general criteria for the distribution of the proof burdens are consistent with one of the most relevant preoccupations of procedural law jurists: the search for more effectiveness in the substantive field by the procedural technique refinement